Meningkatkan Aktivitas, Keterampilan Berpikir Kritis, Dan Hasil Belajar Muatan PPKn Kelas IV A Menggunakan Model Pesat Di SDN Manarap Lama 1 - Nabilla Azahra; Fathul Jannah (Pusat Riset dan Inovasi Nasional, 2023)
The research aims to address the issue of low activity, critical thinking skills, and learning outcomes in students. To overcome this problem, the PESAT model is introduced in the learning process. The study focuses on teacher activities, student activities, critical thinking skills, and student learning outcomes. The research employs Classroom Action Research (PTK) and is conducted at three meetings. The subjects are students from Class IV A of SDN Manarap Lama 1 in the second semester of the 2022/2023 academic year, with a total of 22 students. The research uses a combination of qualitative and quantitative approaches. Data analysis involves descriptive techniques, with results presented in tables, graphs, and percentages. The findings indicate that educators' activities receive a score of 32 based on the